A Literature Review of Students’ Difficulties in Quadratic Equations and Problem-Solving Learning Using LKPD : Penelitian - Nazwa Mutia Syafitri; Helina Qatrunnada Nasution; Khalida Rahmah; Dian Armanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Quadratic equations are an essential topic in mathematics education because they contribute to the development of students’ analytical thinking and problem-solving abilities. However, many students still experience difficulties when solving quadratic equation problems. These difficulties are often related to limited conceptual understanding, challenges in interpreting mathematical problems, and mistakes in applying algebraic procedures. This study aims to identify the difficulties encountered by students in solving quadratic equations and to examine the role of a problem-solving learning model assisted by Student Worksheets (LKPD) in improving students’ mathematical problem-solving abilities. This research employed a literature review method by systematically identifying, selecting, and analyzing relevant studies published in academic journals. The results indicate that students frequently struggle to understand problem contexts, translate problems into mathematical representations, and apply systematic solution strategies. Furthermore, the integration of a problem-solving learning model supported by LKPD can facilitate structured learning activities, strengthen conceptual understanding, and improve students’ mathematical problem-solving competence.